Penguatan Strategi Penghimpunan ZIS di BAZNAS Kabupaten Sleman - Asmuni Asmuni (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
The increase in the amount of ZIS fundraising greatly impacted the welfare of the Ummah. For this reason, this community service activity aims to socialize the device strategy for implementing ZIS fundraising at BAZNAS, Sleman district, which has experienced an increase. Service activities are carried out using the method of socializing the zakat awareness movement directly to the community, opening consulting services online and offline, as well as conducting zakat role models which are expected to make people understand or be aware of the obligation to pay zakat. The results of community service activities include several strategies carried out by BAZNAS of Sleman Regency in raising ZIS funds, namely: 1) The strategy of awareness socialization of the zakat movement and related provisions can influence the muzaki's decision to pay zakat. 2) Opening an online zakat consulting service in the form of via WhatsApp and in-person consultation at the Sleman district BAZNAS office also has a significant impact on Muzaki. 3) Carry out the role model zakat movement every month, which also influences the muzaki's decision to pay zakat. It was concluded that the socialization of the Zakat awareness movement, consulting services related to Zakat, and the role model Zakat movement had a positive impact and succeeded in strengthening the ZIS fundraising process.